2002
DOI: 10.1292/jvms.64.761
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Lignan-Containing Flaxseed Extract against CCl4-Induced Hepatic Injury.

Abstract: ABSTRACT. Carbon tetrachloride (CCl 4 ) -induced hepatotoxicity is a commonly used model for investigating lipid peroxidation-related tissue injury. In the present study, the effect of flaxseed extract was observed on histological sections, glutathione-content and DNA strand breaks. Lignan-containing flaxseed extract (1.6 g/kg body weight/day) was daily administered with intragastric injection to rat s for three days, on the fourth day, CCl 4 (2 g/kg) was intraperitoneally injected. Liver tissue was sampled at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
6
15
0
Order By: Relevance
“…SDG and pinoresinol are reported to have strong antioxidative effects (Harper et al, 1999). The present study supports the findings of Endoh et al (2002) who found that flaxseed extract inhibited the CCl 4 induced decrease in levels of reduced glutathione in rat liver. Flaxseed oil has a high content of alpha linolenic acid and is marketed as a health food, although indirect evidence suggests that the omega-3 fatty acid in flaxseed oil is not effective in lowering serum lipids and hypercholesterolemic atherosclerosis in rabbits (Lee and Prasad, 2003).…”
Section: Resultssupporting
confidence: 91%
“…SDG and pinoresinol are reported to have strong antioxidative effects (Harper et al, 1999). The present study supports the findings of Endoh et al (2002) who found that flaxseed extract inhibited the CCl 4 induced decrease in levels of reduced glutathione in rat liver. Flaxseed oil has a high content of alpha linolenic acid and is marketed as a health food, although indirect evidence suggests that the omega-3 fatty acid in flaxseed oil is not effective in lowering serum lipids and hypercholesterolemic atherosclerosis in rabbits (Lee and Prasad, 2003).…”
Section: Resultssupporting
confidence: 91%
“…This latter effect appears due to the enhancement in the functioning of the hepatic GSH antioxidant system, possibly through stimulating the activities of GSH-related enzymes. 40,41 The study by Endoh 42 purports to show a protective effect of a flaxseed extract on CCl 4 liver damage. Further, this protection is expressed as an attenuation of the CCl 4 -induced decrease in liver GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations by Thompson have shown that flaxseed's lignan, secoisolariciresinol diglucoside (SDG) has a colon cancer protective effect [73,74]. A study using flaxseed-extract has also shown to protect liver cells against carbon tetrachloride -induced necrosis [75]. Whereas SDG lignan is also considered a powerful antioxidant, rosemary herb is known as one of nature's most powerful antioxidants [76].…”
Section: Cancer Chemopreventive Herbs and Spicesmentioning
confidence: 99%